(3YLGdI GdbQi aj JGQjN Ge GdbQis - (3eMeO Hf CMeO Hf Ydj, Jbj GdOjf, CHh GdWjH Gdecqj GdMSfj, J (B832 (3g` s ((3ecI s)
(3ChdgG (B:s
(3Chd GdehLhO ef GdebOeI (B: (3hCeG GdJQGLe agi JQGLe LeGYI ef GdGYjGf ef Ggd ecI hZjQge eef ScfgG eOI Sfjf Gh eGJ ajgG s
(3BNQgG (B:s
(3heG XaQ GdaJi ai GdOgQ heG HCWjH ef eLGhQI GdcQGe hbO GfJgi s
(3hHChd agQS hHChQGbgG fbU hGVWQGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B300s
Keywords: (3eJaQbGJs